The comparison of Health status and Health services utilisation between Indigenous and Non-Indigenous infants in Australia - Chen, J; Ou, L; Eastwood, J; Hillman, K (My University, 2010)
Drawing upon data from the Longitudinal Study of Australian Children, this article compares the health service attendance between Indigenous and non-Indigenous infants in Australia. Infant, maternal, family, and neighbourhood characteristics were examined, as well as types of health care services. The analysis found that Indigenous infants were significantly less likely to use maternal and child health centres, general practitioners, and paediatricians, but more likely to use hospital outpatient clinics. These rates were associated with mothers' characteristics , financial status, and residential location.
Keywords: Culture -- Indigenous; Culture; Health; Health -- Access to services; Health and wellbeing; Health; Culture; Indigenous; Access to services; Health and wellbeing